Designing Web-based training : how to teach anyone anything anywhere anytime - Horton, William K. (New York : Wiley, 2000)
The surge in the number of online training sites has created an unprecedented demand for experts who know all aspects of Web-based training (WBT) site design. Written by bestselling author William Horton, this book provides the hands-on and practical guidance that trainers demand. Packed with over 100 examples, this well-illustrated guide walks you through every phase of designing WBT, from analyzing your course requirements and assessing the needs of potential students to designing a course for a global audience. You'll find out how to combine elements into effective and interesting learning sequences, discover how to overcome any technical hurdle that may arise, how to offer materials that motivate learning, and how to use Web technologies to create 21st-century alternatives to traditional courses. Praise for Designing Web-Based Training "Horton has done it again! He's addressed the cutting-edge problem of Web-based training design with his pragmatic, research-based approach. His work is task-oriented and down-to-earth. He doesn't waste our time with excessive educational philosophy. In short-comprehensive overview, practical advice, engaging presentation."-Robert E. Horn, Author, Visual Language: Global Communication for the 21st Century "As each new media wave is adopted for instructional pur-poses, there is a lag in effective exploitation of the unique features the medium brings for supporting learning. Designing Web-Based Training bridges the gap by providing a rich and detailed reference."-Ruth Clark, EdD, President, Clark Training & Consulting "Designers have been seeking guidance on how to exploit the Web's distribution potential while combining it with powerful instructional programs. Horton provides structure, stimulation, and substance in this important book. Web-based training is definitely what is happening now. Designing Web-Based Training will be a de facto classic in the field." -Gloria Gery, Principal, Gery Associates, Author, Making CBT Happen The companion Web site at www.wiley.com/compbooks/horton/ features: Design guidelines Live versions of many examples from the book A course shell and sample lessons Links to helpful references.
Includes bibliographical references and index.
Keywords: Employees -- Training of -- Computer-assisted instruction; World Wide Web